PROCESOS CONSTRUCTIVOS Y ESTRUCTURALES DE LA ARQUITECTURA DE LOS SIGLOS XVI, XVII, XVIII Y XIX EN INMUEBLES PATRIMONIO CULTURAL - Gallegos Cornejo, Juan Carlos; Juárez Sandoval, Eloy (JÓVENES EN LA CIENCIA, 2015)
Considering the importance of historical studies of construction, we did a documentary investigation of the characteristics and construction methods of builds from the centuries XVI, XVII, XVIII and XIX. Research excels in this period the basis of the procedures used today settled like masonry and some technics of foundation. Build is the mirror of the society. Constructions of XVI show the cultural mix. And at century XVIII show the identity develop. Although observed characteristics that are recurrent in the centuries studied. Each century have own particularities. among which we can mention the genres most favored in every century. For example Religious constructions are the most common at the colony, but at century XIX the most common constructions are civilians. The historic studies allowed identify the evolution of structural design bases. Sometimes the changes are very drastic. Such is the case of the foundation, which, even if the techniques used in the colony are the basis of current processes, its design was based on a different idea.